2011
DOI: 10.1007/s00436-011-2580-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and overexpression of transferrin gene from cypermethrin-resistant Culex pipiens pallens

Abstract: The complete sequence of transferrin has been cloned from cypermethrin-resistant strain of Culex pipiens pallens(Cr-C strain). Quantitative reverse transcription PCR analysis indicated that the transferrin transcription level was 12.6 times higher in Cr-C strain than in susceptible strain at fourth instar larvae. The transferrin expression was also found to be consistently higher throughout the life cycle of Cr-C strain. A protein of predicted size 90.8 kDa has been detected by Western blotting in transferrin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…3 C). There have been no reports of plant secondary chemicals inducing the expression of transferrin, but some have suggested that transferrin is expressed at higher levels in cypermethrin-resistant strains and that this may confer insecticide resistance in C. pipiens pallens (Tan et al ., 2012 ). dsRNA-mediated depletion of HaTrf in second-instar larvae decreased their tolerance to 2-tridecanone (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 C). There have been no reports of plant secondary chemicals inducing the expression of transferrin, but some have suggested that transferrin is expressed at higher levels in cypermethrin-resistant strains and that this may confer insecticide resistance in C. pipiens pallens (Tan et al ., 2012 ). dsRNA-mediated depletion of HaTrf in second-instar larvae decreased their tolerance to 2-tridecanone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have indicated that transferrin-transfected cells also show enhanced cypermethrin resistance compared with null-transfected or plasmid vector-transfected cells, as determined by methyl tritiated thymidine ( 3 H-TdR) incorporation. These results indicate that the expression of transferrin could be induced by the xenobiotic cypermethrin in the resistant strains, and that transferrins might confer insecticide resistance in C. pipiens pallens (Tan et al ., 2012 ; Vezilier et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transferrin ( Tf1 - AAEL015458), found to be under expressed in temephos resistant larvae in the current study, also has roles in the innate immune response to arbovirus infection [98, 103] and has previously been reported to be downregulated in CHIKV and DENV infected mosquitoes which may favour viral replication [104]. Transferrin expression has also been related to insecticide resistance in Culex pipiens with increased expression reported in mosquitoes with target-site resistance to pyrethroids and organophosphates, the biggest difference in transferrin expression was observed in adults [105, 106].…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, searches of the ten most highly expressed genes from these previous studies with our data found that none of these previously identified genes were overexpressed in our resistant strains. Candidate genes previously associated with pyrethroid resistance in other species of mosquitoes include transferrin [ 82 ], iron responsive element binding protein [ 83 ], glycogen branching enzyme [ 84 ], chymotrypsin [ 82 ] and G-protein coupled receptor [ 85 ]. None of these genes were overexpressed in our resistant strains, leading us to conclude that they do not play a role in pyrethroid resistance in CKR or SP.…”
Section: Discussionmentioning
confidence: 99%